2012
DOI: 10.1093/ejcts/ezr029
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve replacement with and without combined coronary bypass grafts in very elderly patients: early and long-term results

Abstract: In our experience, a careful pre-operative evaluation has yielded good surgical results even in older patients with different comorbidities. Associated coronary grafts slightly increase the surgical risk. The role of revascularization on long-term morbidity and mortality is still not clear. It is essential to compare the results of percutaneous and trans-apical aortic valve replacement with the literature results of conventional aortic valve replacement with and without CABG before it can be used as an alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 24 publications
4
24
0
2
Order By: Relevance
“…In contrast, some studies found that outcomes were the same or better after AVR with CABG compared with AVR alone [7][8][9]. Melby et al [13] found that concomitant CABG improved operative and long-term outcomes in elderly patients undergoing AVR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, some studies found that outcomes were the same or better after AVR with CABG compared with AVR alone [7][8][9]. Melby et al [13] found that concomitant CABG improved operative and long-term outcomes in elderly patients undergoing AVR.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported higher rates of operative mortality and morbidity in elderly patients after combined AVR and CABG compared with AVR alone [2][3][4][5][6]. In contrast, other studies reported similar outcomes after AVR with or without CABG [7][8][9]. All these studies reported comparisons between AVR alone vs combined AVR and CABG in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, they found that the urgency status, EF <35%, intraoperative variables (such as the clamping time and need for an intra-aortic balloon pump) and postoperative variables (such as prolonged ventilation, dialysis, postoperative myocardial infarction, and repeat thoracotomy for bleeding) had an influence on hospital mortality. 8) Although there have been few reports regarding AVR in Japanese elderly patients, Handa et al investigated 7883 patients undergoing isolated AVR in the Japan Adult Cardiovascular Surgery Database. They found that operative mortality andthe incidence of postoperative complications (stroke, respiratory problems, transient ischemic attack (TIA), renal failure, multiple organ failure, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Among patients who underwent AVR in combination with CABG, the history of myocardial infarction was more often recorded, neurological deficit and multifocal atherosclerosis; in the intraoperative period, the time of aortic clamping was higher, and in the postoperative period, the low cardiac output syndrome was more often registered (early outcomes -18.6% in group AVR+CABG, compared with 4.8% in group AVR). Differences in results, according to the authors, are due to the initial clinical characteristics of patients (17). In Norway, during the same period, the proportion of patients with ischemic and degenerative mitral insufficiency in whom the CABG and MVR or mitral valve repair were simultaneously performed was 33% while, 13% of patients simultaneously underwent CABG and AVR (18).…”
Section: Vhd Surgery Combined With Cabg In Elderlymentioning
confidence: 94%